Can we expect similar behavior among CuNiTi 35°C wires? - GONZAGA, Ariane Salgado (Dental Press J Orthod, 2021)
OBJECTIVE: This paper aims to verify the thermodynamic, mechanical and chemical properties of CuNiTi 35ºC commercial wires. METHODS: Forty pre-contoured copper-nickel-titanium thermodynamic 0.017 x 0.025-in archwires with an Af temperature of 35°C were used. Eight wires from five different manufacturers (American Orthodontics® [G1], Eurodonto® [G2], Morelli® [G3], Ormco® [G4] and Orthometric® [G5]) underwent cross-sectional dimension measurements, tensile tests, SEM-EDS and differential scanning calorimetry (DSC) tests. Parametric tests (One-way ANOVA and Tukey post-test) were used, with a significance level of 5%, and Pearson’s correlation coefficient test was performed between the Af and chemical elements of the wires. All sample tests and statistical analyses were double-blinded. RESULTS: All wires presented standard dimensions (0.017 x 0.025-in) and superelastic behavior, with mean plateau forces of: G1 = 36.49N; G2 = 27.34N; G3 = 19.24 N; G4 = 37.54 N; and G5 = 17.87N. The Af means were: G1 = 29.40°C, G2 = 29.13°C and G3 = 31.43°C, with p>0.05 relative to each other. G4 (32.77°C) and G5 (35.17°C) presented statistically significant differences between each other and among the other groups. All samples presented Ni, Ti, Cu and Al in different concentrations. CONCLUSIONS: The chemical concentration of the elements that compose the alloy significantly influenced the thermodynamic and mechanical properties.